(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: The prevalence of dysmenorrhea or menstrual pain in various countries around the world varies between 17% and 90%. The prevalence of menstrual pain in Indonesia is estimated at 64.25%. In adolescent girls, the incidence of menstrual pain is estimated to be between 30%-60%, of which 7%-15% result in absenteeism from school. Based on UKS data from Smpn 1 Dusun Tengah, there are 63 female students who experience menstrual pain from class VII-IX. Objektive: To find out the effectiveness of yoga to overcome menstrual pain in young women at Smpn 1 Dusun Tengah . Methods: The research method used was quantitative, carried out in the form of a quasi-experiment (Quasi Experiment). The sample size is the same as the population, namely 182 people using purposive sampling technique. Results: The results of the research conducted showed that before yoga disturbed the activities of 15 respondents (50.0%), it was very disturbing for 9 respondents (30.0%), unbearable for 6 respondents (20.0%). After yoga, 20 respondents (66.7%) were a little sick, 10 respondents (33.3%) were a little bothered. The average effectiveness result before yoga was 7.40 and after yoga 2.67 with a P-Value of 0.000, meaning that there was effectiveness of yoga activities. Conclusion: The effectiveness of yoga in reducing menstrual pain in adolescent girls with an average P-value of 0.000 and is expected to increase the knowledge of adolescent girls to find out the effectiveness of yoga in overcoming menstrual pain in adolescent girls at Smpn 1 Dusun Tengah.